Students' perceptions of using films in literature classroom in the Faculty of Education, UiTM Shah Alam / Mohd Safwan Salleh - Salleh, Mohd Safwan (2012)
Students nowadays grow up in a culture of technology and media, it is best for educators to realize this fact and use it to their advantages. Using films especially is a great way to engage these students to the literary text as they need to be visually driven. Films can be really helpful in the literature classroom. It has the power to stimulate discussion, engage students, increase their ability to think critically and develop students' reflective and communicative skills. This study focused on students' perception of using films in literature classroom in the Faculty of Education, UiTM Shah Alam. It was carried out in order to investigate the way films are used in literature classroom and to identify the strengths and weaknesses of using films in literature classroom. The respondents were Part 3, Part 4 and Part 5 undergraduate TESL students from the Faculty of Education, UiTM Shah Alam. This research used semi-structured interview and questionnaire as the instruments. The findings revealed that the way films are used in literature classroom was quite similar even with many lecturers. The findings also showed that the methods were viewed positively by the students. The findings also revealed that there are many strengths of using films in literature classroom compared to the weaknesses. Educators should incorporate more literature subjects with films and develop better methods of implementing films in the literature classroom in the future.